ENGLAND’S WAR AGAINST THE SOUTH AFRICAN REPUBLICS PART I - Romeiko-Gurko, Colonel (Scientia Militaria - South African Journal of Military Studies, 2012)
Soon after the outbreak of the South African War (1899-1902) the Imperial Russian government sent military attaches to both fighting sides in South Africa. The military attache with the British forces was Lt, Colonel Stakhovich. He was an officer in one of the best Imperial Guard regiments and was probably chosen for that mission on account of his good command of the English language.